Genomic profiling of Streptococcus agalactiae (Group B Streptococcus) isolates from pregnant women in northeastern Mexico: clonal complexes, virulence factors, and antibiotic resistance - Jose Manuel Vazquez-Guillen; Gerardo C. Palacios-Saucedo; Lydia Guadalupe Rivera-Morales; Amilcar Caballero-Trejo; Aldo Sebastian Flores-Flores; Juan Manuel Quiroga-Garza; Rocio Alejandra Chavez-Santoscoy; Jesus Hernandez-Perez; Silvia Alejandra Hinojosa-Alvarez; Julio Antonio Hernandez-Gonzalez; Maurilia Rojas-Contreras; Ricardo Vazquez-Juarez; et al. (PeerJ)
Background Streptococcus agalactiae (Group B Streptococcus, GBS) is an important pathogen associated with neonatal sepsis, pneumonia, and meningitis, which can be transmitted from colonized pregnant women to their newborns. This study aimed to determine the prevalence and characterize the genomic features of S. agalactiae isolates from pregnant women attending a referral hospital in Northeastern Mexico. Methods Vaginal-rectal swabs were collected from pregnant women during routine prenatal care between April 2017 and March 2020. Whole-genome sequencing was conducted to determine sequence type (ST), clonal complex (CC), capsular polysaccharide (Cps) genotype, virulence factors, and antibiotic resistance genes through comparative genome analysis. Results S. agalactiae colonization was detected in 51 (2.7%) of 1,924 pregnant women. The most common STs were ST8 (23.5%) and ST88 (15.7%). Cps genotyping showed high concordance between serological and molecular methods. Genes conferring resistance to tetracyclines (tetM, 60.1%) and macrolides (mreA, 100%) were identified. Key virulence factor genes, including cylE, bca, and scpB, were present in over 90% of the isolates. Conclusion Although GBS colonization prevalence was low, genomic analysis revealed the genetic diversity of S. agalactiae in Northeastern Mexico, emphasizing the importance of molecular techniques for epidemiological surveillance and infection control.